Analysis Of Continuance Intention Factors Among Muslim Pro App Users Using A Modified Expectation Confirmation Model (M-ECM) - Nesha Putri Nazwa; Tri Suratno; Yolla Noverina (Universitas Islam Kuantan Singingi, 2026)
The Muslim Pro application is the digital worship support platform with the highest download rate in Indonesia. Despite its high popularity, the application has experienced a consistent downward trend in ratings due to various technical and content issues. This study aims to analyze the factors influencing users' continuance intention to use the Muslim Pro application by integrating the Information Systems Success Model (ISSM) and the Expectation-Confirmation Model (ECM). This quantitative research involved 161 respondents who are active users in Indonesia, selected through a purposive sampling technique. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS 4 software. The results of testing the 10 hypotheses showed that 6 hypotheses were accepted and 4 hypotheses were rejected. Satisfaction and Perceived Usefulness proved to be the main drivers of Continuance Intention. A unique finding in this study indicates that System Quality does not have a significant effect on Perceived Usefulness or Confirmation due to the high frequency of intrusive advertisement interruptions. It can be concluded that the users' intention to continue using Muslim Pro is purely driven by the functionality of its specific worship features, regardless of the decrease in comfort regarding system quality.